Abusive Supervision, Upward Maintenance Communication, and Subordinates' Psychological Distress - Tepper, Bennett J.; Moss, Sherry E.; Lockhart, Daniel E.; Carr, Jon C. (Academy of Management Journal, 2007)
This study reanalyzes data from Tepper's (2000) two-wave study regarding the effects of subordinates' perceptions of supervisory abuse to assess previously unexamined relationships. As predicted, we found that subordinates who more rather than less strongly perceived that they had been abused by supervisors tended to use regulative maintenance tactics with higher frequency. Further, the positive relationship between abusive supervision and subordinates' psychological distress was exacerbated by subordinates' use of regulative maintenance communications, and that relationship was reduced by subordinates' use of direct maintenance communication. Theoretical and practical implications are discussed.